Jeux poétiques et matérialité : le cas du Caimán Barbudo à Cuba - Amina Damerdji (Tracés, 2015)
The object of this article is the writings of a group of young facetious poets gathered around a journal funded in 1966 in Havana, El Caimán Barbudo (The Bearded Caiman). Their attitude and texts show an original ideological position: while claiming a pure, enthusiastic and genuine revolutionary commitment, they highlight their love for play, casualness and their rejection of gravity, solemnity and seriousness. In front of the extremely serious tone of the discourses of a regime which keeps on reminding the grandeur of the Revolution and the magnitude of the task to accomplish, this playfulness may seem paradoxical. The notion of materialism, defined as a particular – even exclusive – attention given to things of the physical world, might help solve this paradox. Indeed, while being in line with the poets who precede them, the caimans use a kind of mundanity in line with the atheistic materialism of the regime. Nevertheless, the humoristic distance they associate with this mundanity by their poetic games adds a subversive significance to their writings.